2022
DOI: 10.1590/1679-78257157
|View full text |Cite
|
Sign up to set email alerts
|

Stress-strain distribution and failure mechanisms in dual-phase steels investigated with microstructure-based modeling

Abstract: In this study, the microstructural-based finite element modeling of dual-phase steels was investigated to visualize the crack initiation and its propagation through the phases that exist in the material. The parameters of various failure models, including Gurson, Gurson-Johnson-Cook, and Johnson-Cook (JC), were calibrated for different microstructure levels of DP600, DP800, and DP1000 steels. The onset of cracking, nucleation, void growth, and coalescence was determined using the models. As a result of the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…There are also some instances of studying the formability and damage behaviour of multi-phase steel as an application of representative volume elementbased micromechanical modelling in predicting the macro-mechanical behaviour of materials [20,21]. Whereas, the distribution of stress-strain behaviour along with the failure mechanism of dual-phase steels can also be predicted with 2-dimensional representative volume element model [22]. Moreover, with the help of representative volume element based micro-mechanical model it can be shown that the phase composition, grain size, intergranular boundary and its orientation with respect to tensile axis determines the strain partitioning and damage initiation [23].…”
Section: Introductionmentioning
confidence: 99%
“…There are also some instances of studying the formability and damage behaviour of multi-phase steel as an application of representative volume elementbased micromechanical modelling in predicting the macro-mechanical behaviour of materials [20,21]. Whereas, the distribution of stress-strain behaviour along with the failure mechanism of dual-phase steels can also be predicted with 2-dimensional representative volume element model [22]. Moreover, with the help of representative volume element based micro-mechanical model it can be shown that the phase composition, grain size, intergranular boundary and its orientation with respect to tensile axis determines the strain partitioning and damage initiation [23].…”
Section: Introductionmentioning
confidence: 99%